Local Wisdom Based Culinary Tourism Destination for Enhancing Community Income - Dhiasti Eka Wulandari; Naily Rizqy Amaliyah; Gati Ayu Likasari (The Indonesian Accounting Review, 2026)
This study aims to examine the development of culinary tourism based on local wisdom in Karangbendo Village, Lumajang Regency, as an effort to increase community income. The research employs a mixed methods approach with an explanatory sequential design, beginning with the collection of quantitative data through questionnaires distributed to 259 respondents selected using proportional random sampling, followed by qualitative data collection through interviews, observations, triangulation, and documentation. The results show that culinary tourism and local wisdom have a significant influence on increasing community income, both partially and simultaneously, with a contribution rate of 80.1%. Qualitative findings reveal that the spatial operationalization of 'Dalan Tegalan' serves as a primary economic driver, while culinary authenticity and traditional practices function as a unique selling proposition. However, structural challenges in infrastructure and digital literacy remain significant bottlenecks for optimal economic growth. However, several challenges remain, such as limited facilities, low human resource capacity, and suboptimal promotional strategies. Theoretically, this research contributes to the academic discourse on tourism based on local wisdom and its connection to sustainable economic development. Practically, the findings indicate that culinary tourism can serve as an effective strategy for community empowerment through the strengthening of MSMEs, utilization of digital media, product innovation, and collaboration among stakeholders to ensure equitable economic benefits while reinforcing the village's cultural identity.